Peningkatan Pemahaman Peserta Didik terhadap Materi Memahami Struktur Teks Karya Ilmiah Melalui Metode Diskusi Berbasis Kritik Teman Sejawat (Peer Review Disscusions) Siswa Kelas XI SMAN 3 Palembang - Islamiyah, Regita; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the increase in students' understanding of the material in understanding the structure of scientific work texts through a discussion method based on peer review discussions for class XI students at SMA Negeri 3 Palembang. The type of research carried out is Classroom Action Research (CAR) using the Kemmis and Mc Taggart research model. The subjects of this research were students in class XI.2 of SMA Negeri 3 Palembang for the 2023/2024 academic year. The indicator of the success of the action in this research is the cognitive test results of students who succeeded in achieving a KKM score of ≥ 78 or there were more than 80% of students who were complete in understanding the lesson. This research consists of two cycles with one meeting each cycle. Each cycle consists of planning, action, observation and reflecting stages. Data analysis techniques use quantitative and qualitative data analysis techniques. The results of the research showed that in the first cycle, the results of the cognitive test of students' understanding showed that of the 45 students, there were 28 (68.2%) students who scored above the KKM, and 17 (37.8%) students had not yet achieved KKM value. This means that, after implementing the peer review discussion method, students' understanding of the material in understanding the structure of scientific work texts has increased but has not yet reached the successful indicator of research completion. Therefore, researchers continued research in cycle II. In cycle II there was a significant increase in the results of students' cognitive understanding tests with 43 (95.5%) students getting a complete score above the KKM and 3 (6.6%) students who had not yet reached the KKM score.